High Proton Conductivity in a Flexible, Cross-Linked, Ultramicroporous Magnesium Tetraphosphonate Hybrid Framework - Pérez-Colodrero, Rosario Mercedes; Olivera-Pastor, Pascual; Losilla, Enrique R.; Hernández Alonso, Daniel; García-Aranda, Miguel Ángel; León-Reina, Laura; Rius, Jordi; Demadis, Konstantinos D.; Moreau, Bernard; Villemin, Didier; Palomino, Miguel; Rey, Fernando; et al. (American Chemical Society, 2012)
Multifunctional materials, especially those combining two or more properties of interest, are attracting immense attention due to their potential applications. MOFs, metal organic frameworks, can be regarded as multifunctional materials if they show another useful property in addition to the adsorption behavior. Here, we report a new multifunctional light hybrid, MgH6ODTMP·2H2O(DMF)0.5 (1), which has been synthesized using the tetraphosphonic acid H8ODTMP, octamethylenediamine-N,N,N′,N′-tetrakis(methylenephosphonic acid), by highthroughput methodology. Its crystal structure, solved by Patterson-function direct methods from synchrotron powder Xray diffraction, was characterized by a 3D pillared open framework containing cross-linked 1D channels filled with water and DMF. Upon H2O and DMF removal and subsequent rehydration, MgH6ODTMP·2H2O (2) and MgH6ODTMP·6H2O (3) can be formed. These processes take place through crystalline−quasi-amorphous−crystalline transformations, during which the integrity of the framework is maintained. A water adsorption study, at constant temperature, showed that this magnesium tetraphosphonate hybrid reversibly equilibrates its lattice water content as a function of the water partial pressure. Combination of the structural study and gas adsorption characterization (N2, CO2, and CH4) indicates an ultramicroporous framework. High-pressure CO2 adsorption data are also reported. Finally, impedance data indicates that 3 has high proton conductivity σ = 1.6 × 10−3 S cm−1 at T = 292 K at ∼100% relative humidity with an activation energy of 0.31 eV.
Keywords: Química inorgánica; Magnesium Tetraphosphonate; X-ray diffraction; Metal phosphonates; Proton conductivity